2017
DOI: 10.1002/jnr.24016
|View full text |Cite
|
Sign up to set email alerts
|

Cortical hemorrhage‐associated neurological deficits and tissue damage in mice are ameliorated by therapeutic treatment with nicotine

Abstract: Intracerebral hemorrhage (ICH) is associated with diverse sets of neurological symptoms and prognosis, depending on the site of bleeding. Relative rate of hemorrhage occurring in the cerebral cortex (lobar hemorrhage) has been increasing, but there is no report on effective pharmacotherapeutic approaches for cortical hemorrhage either in preclinical or clinical studies. The present study aimed to establish an experimental model of cortical hemorrhage in mice for evaluation of effects of therapeutic drug candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Macrophage M1/M2 polarization have been identified in various central nervous system diseases, such as traumatic brain injury, spinal cord injury, and ischemic stroke [25][26][27]. The activation of macrophages occurs in the hemorrhagic brain and leads to inflammatory damage following ICH [28][29][30]. However, the specific mechanisms underlying macrophage polarization following ICH have not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage M1/M2 polarization have been identified in various central nervous system diseases, such as traumatic brain injury, spinal cord injury, and ischemic stroke [25][26][27]. The activation of macrophages occurs in the hemorrhagic brain and leads to inflammatory damage following ICH [28][29][30]. However, the specific mechanisms underlying macrophage polarization following ICH have not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine, an agonist of the α−7 nicotinic acetylcholine receptor (α7-nAChR), has been investigated in several animal models of ICH as a potential neuroprotective agent that mediates the cholinergic anti-inflammatory pathway. [8][9][10][11][12] These studies reported decreased neuronal cell death and infiltration of inflammatory cells into the perihematomal area in subjects administered an α7-nAChR agonist, with resultant improvements in sensorimotor function and animal survival. [9][10][11][12] Despite its many detrimental consequences, including potential associations with increased ICH risk, cigarette smoking may have paradoxical neuroprotective effects in patients presenting with ICH via the cholinergic anti-inflammatory pathway mediated by the nicotine content found in cigarettes.…”
Section: -7mentioning
confidence: 99%
“…[8][9][10][11][12] These studies reported decreased neuronal cell death and infiltration of inflammatory cells into the perihematomal area in subjects administered an α7-nAChR agonist, with resultant improvements in sensorimotor function and animal survival. [9][10][11][12] Despite its many detrimental consequences, including potential associations with increased ICH risk, cigarette smoking may have paradoxical neuroprotective effects in patients presenting with ICH via the cholinergic anti-inflammatory pathway mediated by the nicotine content found in cigarettes. [13][14][15][16][17][18][19] However, the relationship between smoking status and post-ICH outcomes has not been rigorously investigated.…”
Section: -7mentioning
confidence: 99%
“…On the other hand, the relative incidence of non-hypertension-associated ICH that occurs in the cerebral cortex (cortical or lobar hemorrhage) has been increasing in recent years, but therapeutic approaches for cortical hemorrhage have been poorly explored. We addressed whether nicotine can provide therapeutic effect in cortical hemorrhage in mice (Anan et al 2017). Collagenase injection into the parietal cortex induced hemorrhage, which resulted in motor deficits in mice.…”
Section: Effects Of Nachr Agonists On Intracerebral Hemorrhage (Ich)mentioning
confidence: 99%